Framing of Papua Under Two Different Medias: Tirto.id and Reuters of United States - Almas Rifqi Darmawan (Department of Languages and Literature, Faculty of Cultural Sciences, UGM, 2019)
Critical discourse analysis (CDA) is a bridge of interpretations through textual context occurred in the news media. Thus, the 2019 Papua’s issues were getting a huge portray in online news and many news coverages in national and international level that had put Papua issues into bias. Media’s framing influences people perception as a reader. Under CDA and the framing of Papua, the news readers are expected to have their own perception through the media’s perspectives or frames. Qualitative method was used to uncover the frames of the online news media of Tirto.id and Reuters of United States. This research explores how Tirto.id and Reuters are framing the Papua issue in their articles by defining the types of frames occurred in both news media within the period. Following the framing categorization which are conflict frame, human interest frame, responsibility frame, and consequences frame and by focusing on the wordings which showing the category thus classified them based on the embedded value behind the words. Thus, distinguish the differences of the frames used between both media. The result of the analysis is that in both media employed the frames. One news could contain more than one frame employed. The conclusion is that one news article may portray many frames and both media may indicate two different perceptions of Papua issue under two different circumstances Tirto.id and Reuters of United States.